A Framework to Assess Readiness of Firms for Cloud Manufacturing - Jayasekara, Deepesh Chathuranga (2018)
Nowadays, manufacturing sector is undergoing a massive disruption, making it difficult for manufacturing businesses to survive in the fiercely competitive global market without a support from latest information technologies (IT) and computer aided capabilities. Moreover, advancement of sophisticated technologies such as bigdata analytics, cyber physical systems (CPS), Industrial Internet of things (IIoT), Internet of Services (IoS), computer integrated manufacturing (CIM), and ubiquitous manufacturing systems (UMS) have accelerated digital manufacturing transformation and have added more value to tons of data generated by modern-day machinery, manufacturing equipment and processes, making them smarter and autonomous. To reap the most out of such technological enhancements in the manufacturing sector, bringing cloud technologies into manufacturing is more promising than ever before. Combining the power of intelligent technologies and virtualizing distributed manufacturing resources and capabilities into a cloud-based virtual manufacturing environment and encapsulating as customer centric services is the latest development in manufacturing. Many researchers believe, this disruptive technology, Cloud Manufacturing (CMfg), will give life to ‘Design Anywhere and Make Anywhere’ concept and open doors of efficient, high quality manufacturing to a larger audience. Successful widespread implementation of CMfg depends on the readiness of organisations for CMfg transformation. The purpose of this research is to identify factors affecting CMfg readiness, key characteristics, core business processes and manufacturing requirements required to transform traditional manufacturing firms into CMfg enabled enterprises. This research aims to develop a Cloud Manufacturing Readiness Assessment Framework (CMfg-RAF) which comprises 06 core dimensions: Services, Manufacturing, Operations, Business, Strategy, and Legal, which cover all aspects of a CMfg business environment. Core dimensions are further divided into 36 sub-dimensions which are assessed under 04 readiness levels: Novice, Learner, Experienced, and Master. Last but not least, it presents the readiness criteria that must be fulfilled by sub-dimensions to reach expected readiness levels. Undoubtedly, the results of this research are useful for both academia and industry. Academia can use the readiness assessment framework as a foundation to develop questionnaires and quantitatively assess the readiness of manufacturing firms, to develop case studies covering all aspects of a CMfg business environment presented in the framework, to develop readiness assessment toolkits, etc., whereas, industry decision makers can use the framework to understand CMfg requirements, current readiness levels of companies and as a concise guide to achieve higher readiness levels in future. Main contributions of this research include, furthering the knowledge base in CMfg by fulfilling a critical gap in literature, introducing a comprehensive CMfg-RAF and creating a path to future developments in ‘CMfg Readiness Assessment’ research.